ACTUAL ISSUES OF EXEMPTION FROM CRIMINAL LIABILITY OR PUNISHMENT OF MINORS IN SOME FOREIGN COUNTRIES - Turabaeva Ziyoda Yakubovna (International Journal of Business, Law and Political Science, 2024)
This article discusses the integration and enhancement of juvenile justice systems with a focus on legal reforms. It emphasizes the need to improve national legislation on juvenile offenders by adopting international best practices and probation measures. The study highlights that existing penalties, such as fines and community service, lack sufficient educational impact and fail to prevent recidivism effectively. It proposes incorporating probation measures to ensure more comprehensive rehabilitation and supervision. This approach involves collaboration with educational institutions, psychological support, and social services to foster law-abiding behavior and successful reintegration of juveniles. By integrating these measures into criminal legislation, the goal is to achieve a more effective response to juvenile crime, promote rehabilitation, and prevent future offenses, thereby enhancing the overall juvenile justice system